Topics in the Superconductivity of Simple Metals and Alloys - Trofimenkoff, Peter Nicholas (My University, 1969)
The effects of hydrostatic pressure on the superconducting transition temperatures of the simple metals aluminum, lead, mercury, tin and indium are investigated within the strong-coupling theory of superconductivity. The experimental variation of the transition temperature with volume change can be understood within a simple scaling model. Strong-coupling effects in the pressure dependence of superconductivity in lead and mercury are investigated.
A formalism which includes effects of force constant disorder on superconductivity in a binary alloy of simple metals is established within pseudopotential theory.
Keywords: superconductivity, simple metals, alloys, hydrostatic pressures, aluminum, lead, mercury, tin, temperatures